The Absent presence of the state in large-scale resource extraction projects - Bainton, Nicholas A.; Skrzypek, Emilia E. (Asia-Pacific environment monographs., 2021)
Standing on the broken ground of resource extraction settings, the state is sometimes like a chimera: its appearance and intentions are misleading and, for some actors, it is unknowable and incomprehensible. It may be easily mistaken for someone or something else, like a mining company, for example.